2021
DOI: 10.1080/02640414.2021.1881301
|View full text |Cite
|
Sign up to set email alerts
|

Expert opinion on classification for footballers with vision impairment: Towards evidence-based minimum impairment criteria

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…It was identified that as VIs impact golfing performance, the inclusion criteria were too stringent, allowing only golfers with VI in the B1 to B3 classes to compete. Concerns were also present that widening the inclusion criteria would allow athletes to compete whose VI did not affect their performance, as has been the case for footballers and judokas 9,19 . To achieve fair inclusion criteria, it is necessary to identify at what level VI starts to affect performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was identified that as VIs impact golfing performance, the inclusion criteria were too stringent, allowing only golfers with VI in the B1 to B3 classes to compete. Concerns were also present that widening the inclusion criteria would allow athletes to compete whose VI did not affect their performance, as has been the case for footballers and judokas 9,19 . To achieve fair inclusion criteria, it is necessary to identify at what level VI starts to affect performance.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is appropriate when little is known about a research area, and therefore, expert opinions are the most reliable data available 18 . Delphi reviews have been utilised in establishing consensus for other VI sports, such as track athletics, judo, football and swimming, 6,8,9,19 as well as other non‐VI disability sports 20–22 …”
Section: Introductionmentioning
confidence: 99%
“…While only blind (5-a-side) football features at the Paralympic Games, the International Paralympic Committee exerts influence on disability football in ensuring the sport's standards are acceptable to the wider Paralympic movement. This was seen recently with IPC-led alterations to blind football's classification system (Runswick et al, 2021) and also the exclusion of cerebral palsy football from the Paralympic Games sporting program (Pavitt, 2019).…”
Section: The Context Of the Disability Football Industry In Europementioning
confidence: 95%
“…Research in VI rifle shooting demonstrated that only one class was necessary in that sport, because functionally blind athletes could perform just as well as athletes with much less impairment, presumably because in that sport they can effectively rely on the auditory feedback used in the sport to guide the rifle [ 8 – 13 ]. Research has also begun in other VI sports including football [ 14 , 15 ], judo [ 16 21 ], skiing [ 22 , 23 ], athletics [ 24 ], goalball [ 25 ], and swimming [ 7 ].…”
Section: Introductionmentioning
confidence: 99%